An integrated approach to the study of heritage sites. - Cutajar, Denis; Farrugia, Pierre-Sandre; Micallef, Alfred (Journal of Cultural Heritage, 2019)
This work describes the integrated multidisciplinary approach taken in the study of the Ħal Saflieni Hypogeum. Measurements of temperature, relative humidity (RH) and carbon dioxide (CO 2) were analysed and cross-compared to identify common trends. In the process, the environmental variables were treated as passive transport scalars in order to identify flow patterns. Subsequently, the measurements were used to set up a computational fluid dynamic (CFD) model of the site. Comparisons between simulated results and measured data allowed not only the identification of the limits of the simulations but also revealed flow patterns that would be hard to recognise otherwise.